2019
DOI: 10.3390/microorganisms7050134
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Vacuum Packaging, Fennel and Savory Essential Oil Treatment on the Quality of Chicken Thighs

Abstract: The aim of the present work was to evaluate the microbiological quality of chicken thighs after treatment by fennel (Foeniculum vulgare) and savory (Satureja hortensis) essential oil, stored under vacuum packaging (VP) at 4 ± 0.5 °C for a period of 16 days. The following treatments of chicken thighs were used: Air-packaging control samples (APCS), vacuum-packaging control samples (VPC), vacuum-packaging (VP) control samples with rapeseed oil (VPRO), VP (vacuum-packaging) with fennel essential oil at concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
(43 reference statements)
3
25
0
Order By: Relevance
“…Raw poultry meat poses a microbiological hazard associated with the appearance of pathogenic bacteria. Among them, the most important are Enterobacteriaceae which can be considered an indicator of microbiological quality of meat [ 30 , 43 , 44 ]. In the present study, the amount of Enterobacteriaceae found in raw non-marinated pectoral muscles was 2.98 log cfu·g −1 ; in muscles subjected to 24-h marinating in buttermilk, the amount of these bacteria was 2.34 log cfu·g −1 ; whereas in raw muscles subjected to 24-h marinating in whey it was 2.68 log cfu·g-1 ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw poultry meat poses a microbiological hazard associated with the appearance of pathogenic bacteria. Among them, the most important are Enterobacteriaceae which can be considered an indicator of microbiological quality of meat [ 30 , 43 , 44 ]. In the present study, the amount of Enterobacteriaceae found in raw non-marinated pectoral muscles was 2.98 log cfu·g −1 ; in muscles subjected to 24-h marinating in buttermilk, the amount of these bacteria was 2.34 log cfu·g −1 ; whereas in raw muscles subjected to 24-h marinating in whey it was 2.68 log cfu·g-1 ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In a roast product marinated with buttermilk for 48 h, 1 species of bacteria was identified and with whey, 3 bacteria species from 2 families were identified ( Figure 2 ). In the study, Kačániová et al [ 30 ] and Kačániová et al [ 44 ] showed a positive effect of the use of essential oils on inhibition of bacterial growth. Similar results were obtained in studies on poultry meat after marinating in natural marinades containing lactic acid bacteria in its own study.…”
Section: Resultsmentioning
confidence: 99%
“…Generated spectra were analyzed on a MALDI-TOF Microflex LT (Bruker Daltonics, Bremen, Germany) instrument using Flex Control 3.4 software and Biotyper Realtime Classification 3.1 with BC-specific software. Criteria for reliable identification were a score of ≥2.0 at species level [9].…”
Section: Identification Of Isolates With Mass Spectrometrymentioning
confidence: 99%
“…Qualitative determination of microorganisms we identified by using the device MALDI-TOF Mass Spectrometry (Bruker Daltonics, Bremen, Germany). The isolates were subcultured on Tryptone soya agar (TSA, Oxoid, Basingstoke, UK) for total plate count, sporulating bacteria (at 30 • C), and coliform bacteria/at 37 • C), TSA 90% with MRS 10% for lactic acid bacteria at 30 • C for 24 h. the criteria for reliable identification were a score of ≥2.0 at the species level [19].…”
Section: Mass Spectrometry Identification Of Isolatesmentioning
confidence: 99%